2011
DOI: 10.1590/s1679-62252011005000003
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions among sympatric zooplanktivorous fish species in volume change conditions in a large, shallow, tropical lake

Abstract: Significant reductions in the water volume of shallow lakes impose a restriction on species segregation promoting more interactions in the trophic relationships. The diets of three closely related zooplanktivorous silversides belonging to the Atherinopsidae species flock of lake Chapala, Mexico, were analyzed at two sites (Chirostoma jordani, C. labarcae, and C. consocium). Diets were described in critical shallow ( La reducción significativa en el volumen de agua de los lagos someros impone una restricción en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…While they rely on zooplankton and fish as their main source of energy, our stable isotope data suggests that they may be also consuming food items with enriched δ 13 C values, relative to δ 13 C values for zooplankton as a group. Moncayo-Estrada et al (2011b) found zooplankton in genera Bosmina, Diaphanosoma, Daphnia, Ceriodaphnia, Diaptomus and Cyclops to be the main food items for C. labarcae, C. consocium and C. jordani. Given the known diet for species of Chirostoma, we expected these fish to have similar δ…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…While they rely on zooplankton and fish as their main source of energy, our stable isotope data suggests that they may be also consuming food items with enriched δ 13 C values, relative to δ 13 C values for zooplankton as a group. Moncayo-Estrada et al (2011b) found zooplankton in genera Bosmina, Diaphanosoma, Daphnia, Ceriodaphnia, Diaptomus and Cyclops to be the main food items for C. labarcae, C. consocium and C. jordani. Given the known diet for species of Chirostoma, we expected these fish to have similar δ…”
Section: Discussionmentioning
confidence: 98%
“…Chirostoma species in Lake Chapala exhibit diverse jaw morphologies and body shapes that suggest different feeding habits among the eight species present in the lake. Evidence from gut content analyses has uncovered differences among species (Moncayo-Estrada et al, 2010, 2011b. In some cases, such differences have been attributed to changing Lake Chapala water levels (Moncayo-Estrada et al, 2011a), but other, fine scale studies have suggested preference of a species for a given zooplanktonic group (i.e., diet dominance of cladocerans vs. calanoid or cyclopoid copepods) (MoncayoEstrada et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this lake has the most important adaptive radiation of atherinopsids in fresh water: The Chirostoma flock consisting of eight species (Barbour, 1973;Barbour & Chernoff, 1984). We selected three species for the analysis -Chirostoma jordani, C. consocium, and C. labarcae -because they are the dominant species within the flock, they belong to the same guild (zooplanktivores), and they are the objective species of the local "charales" fishery (Moncayo-Estrada & Buelna-Osben, 2001;Moncayo-Estrada et al, 2011). Thus, these were expected to have strong population interactions related to the water fluctuations.…”
Section: Introductionmentioning
confidence: 99%